The literary basis of the musical „Adio Chiustenge!” - Inga CEBAN (Dialogica: Revistă de Studii Culturale și Literatură)
The article focuses on a significant aspect of Romania’s musical-theatrical history, namely the musical „Adio Chiustenge!” , composed in 2016 by Dumitru Lupu, a composer from Dobrogea, in close collaboration with poet Carmen Aldea-Vlad, the author of the libretto. Dumitru Lupu was a complex personality: composer, conductor and pedagogue. Music his enjoyed great popularity until present, characterized by a melodiousness and special expressiveness, which shaped him a complex musical profile, of a melodist. In this article, we examine D. Lupu’s creative evolution within the context of Romania’s non-academic musical culture. Additionally, we analyze the aspects of the evolution, composition, and dramaturgy of this musical, which holds an important place in the country’s musical-theatrical history.